SINGKUH: WHERE HUMAN IMAGINATION MEETS TECHNOLOGICAL SOUND EXPERIMENTATION - Putri, Ni Made Ayu Dwara; Rafa, Damay Nouvanala Radja (UPT Pusat Penerbitan LP2MPP ISI Bali, 2024)
“Singkuh” is an experimental music composition based on the Balinese concept of